2008
DOI: 10.1002/pds.1702
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption among Canadians taking benzodiazepines and related drugs

Abstract: Heavy alcohol use is uncommon among users of BZDs, and the combination of alcohol and BZD use is rare in the general population. Differences between BZD users and others are not large when other factors are taken into account, however, which may call into question the effectiveness of physician and pharmacist warnings against this combination. People treated for an anxiety disorder with BZDs may be less likely to use alcohol than those taking them for other indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…Ten of the included studies were conducted in Europe [14, 19, 21–23, 25, 2729, 36], eight in North America [18, 20, 24, 3032, 34, 35] and two in Australia [26, 33]. (Table 1) All studies were cross-sectional [14, 1836].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten of the included studies were conducted in Europe [14, 19, 21–23, 25, 2729, 36], eight in North America [18, 20, 24, 3032, 34, 35] and two in Australia [26, 33]. (Table 1) All studies were cross-sectional [14, 1836].…”
Section: Resultsmentioning
confidence: 99%
“…(Table 1) All studies were cross-sectional [14, 1836]. Study settings varied across studies with; community-dwelling [14, 19, 21–27, 31, 3436], both community dwelling or living independently in care facilities [32], general populations [20, 28, 33], hospital setting [29], retirement communities [18] and participants signed up to a pharmaceutical assistance contract for the elderly [30] reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multivariate logistic regression was used to identify the motives associated with past 12-month SSAU, adjusting for other covariates (age, gender, ethnicity, and education), selected based on prior literature suggesting their association with sedative misuse/combined use of sedatives and alcohol (18,19). Furthermore, it is possible that individuals may also have combined sedatives with other drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Although literature about the interactions between psychotropic medications and alcohol in Canada is sparse, one Canadian study reported the prevalence of heavy alcohol consumption among benzodiazepine users in the previous week as 7.2%; current benzodiazepine users were less likely than non-current users to have recently consumed any alcohol. 9 Psychotropic medications are often prescribed for long-term treatment of chronic mental health conditions; as such, it is important for patients to understand the serious negative consequences and risks that may result from alcohol-drug interactions. Health care professionals, such as physicians, nurses, and pharmacists, may give patients information related to their medications.…”
Section: Introductionmentioning
confidence: 99%